GROWTH AND YIELD OF WATERMELON (Citrullus vulgaris) IN SUBSURFACE FERTIGATION USING CLAY POT ON ALFISOL AND ENTISOL - Sutarno; Rahayu; Nurul Farahin; Aktavia Herawati; Komariah; Ganjar Herdiansyah; Mujiyo; Geun Mo Yang (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
This study aims to identify the effect of spacing from subsurface irrigation sources and soil type on the growth and yield of watermelon plants. The research was carried out in the experimental field in Sukosari Village, Karanganyar Regency, with sub-irrigation using clay pots. The experiment used a nesting design with 2 types of soil, namely Alfisol (T1) and Entisol (T2), and the spacing of 4 plants from clay pots was 5 cm (J1), 10 cm (J2), 15 cm (J3), and 20 cm. cm (J4). The research data were analyzed by ANOVA, and if it had a significant effect, then Duncan's test was continued, at a 95% confidence level. The results showed that the treatment of jatropha affected the growth and yield of watermelon plants. Planting distance of 5 cm caused plant height, fruit weight, shoot fresh weight, and shoot dry weight to be higher than other treatments. The type of soil that produced the best watermelon plants was Entisol soil were plant height, shoot fresh weight, and shoot dry height were higher than in Alfisol soil, but for fruit weights the two were not much different.